1991
DOI: 10.1128/mcb.11.3.1185-1194.1991
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor β1 Inhibition of p34cdc2 Phosphorylation and Histone H1 Kinase Activity Is Associated with G1/S-Phase Growth Arrest

Abstract: Transforming growth factor beta 1 (TGF beta 1) is a potent inhibitor of epithelial cell proliferation. We present data which indicate that epithelial cell proliferation is inhibited when TGF beta 1 is added throughout the prereplicative G1 phase. Cultures become reversibly blocked in late G1 at the G1/S-phase boundary. The inhibitory effects of TGF beta 1 on cell growth occur in the presence of the RNA synthesis inhibitor 5,6-dichloro-1-beta-D-ribofuranosylbenzimidazole. Associated with this inhibitory effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Unlike other growth factors such as EGF, PDGF, and NGF, whose responses are very rapid, TGFβ is a relatively slower acting growth factor. TGFβ inhibits cell proliferation in late G1 phase of the cell cycle, and its effects on various cell cycle associated cyclin proteins are not seen until 16 h posttreatment (Howe et al, 1991;Reddy et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other growth factors such as EGF, PDGF, and NGF, whose responses are very rapid, TGFβ is a relatively slower acting growth factor. TGFβ inhibits cell proliferation in late G1 phase of the cell cycle, and its effects on various cell cycle associated cyclin proteins are not seen until 16 h posttreatment (Howe et al, 1991;Reddy et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…The mink lung epithelial cell line, CCL64, is highly sensitive to TGFβ and is routinely used to study TGFβinduced cellular responses (Howe et al, 1991;Reddy et al, 1994). It was of interest, therefore, to determine the effects of TGFβ on both apoJ mRNA and its protein in this cell line.…”
mentioning
confidence: 99%
“…Recently, it has been demonstrated that the RI receptor, in a genetic screening analysis using the two-hybrid system, interacts with the rapamycin binding protein FKBP-12 (Wang et al, 1994). The physiological significance of such binding is unclear; however, the fact that both TGFβ (Howe et al, 1991) and rapamycin (Morice et al, 1993) rapamycin share common signaling components. We also utilized the two-hybrid system (Fields & Song, 1989) to identify receptor-associated proteins but, instead of the RI TGFβ receptor, performed our genetic screen with the cytoplasmic domain of the RII receptor.…”
Section: Resultsmentioning
confidence: 99%